Diccionario de dificultades del inglés - Torrents dels Prats, Alfonso (Juventud, 1976)
Keywords: Dicionarios de dúbidas; Dicionarios ingleses; Gramática; Inglés (Lingua)

English Collocations in Use Advanced Book with Answers: How Words Work Together for Fluent and Natural English - O'Dell, Felicity; McCarthy, Michael (Cambridge University Press, 2017)
Keywords: Colocacións; Estudo e ensino; Inglés (Lingua)

A Communicative Grammar of English - Leech, Geoffrey; Svartvik, Jan (Routledge, 2015)
Keywords: Gramática; Inglés (Lingua); Manual

Test your English vocabulary in use. Advanced - McCarthy, Michael (Cambridge University Press, 2013)
Keywords: Estudo e ensino; Inglés (Lingua); Vocabulario

English for academic study: Vocabulary - Campbell, Colin (Garnet, 2012)
Keywords: Estudo e ensino; Inglés (Lingua); Vocabulario

Objective First Workbook with Answers with Audio CD - Capel, Annette; Sharp, Wendy (Cambridge University Press, 2012)
Third edition of the best-selling Cambridge English: First (FCE) course. The syllabus for this exam has changed and this book has now been replaced by 9781107628458 Objective First Fourth edition Workbook with answers with Audio CD.
Google-Books-ID: w4Yhla97DsoC
Keywords: Estudo e ensino; Gramática; Inglés (Lingua); Manual

English accents & dialects: an introduction to social and regional varieties of English in the British Isles - Hughes, Arthur (Hodder Education, 2012)
Keywords: Acentos e acentuación; Gran Bretaña; Inglés (Lingua); Pronunciación

Compare and Contrast: An English Grammar for Speakers of Spanish - Mackenzie, J L; Martínez Caro, E (Comares, 2012)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

Oxford English Grammar Course. Intermediate (with answers) - Swam, Michael; Walter, Catherine (Oxford University Press, 2011)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua); Manual

Advanced Grammar in Use. A self-study reference and practice book for advanced students of English with answers - Hewings, Martin (University Press, 2009)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

Britain for Learners of English: understand the country and its people - O'Driscoll, J (Oxford University Press, 2009)
Keywords: Cultura; Enciclopedias; Gran Bretaña; Inglés (Lingua)

Advanced grammar in use: a self-study reference and practice book for advanced learners of English ; with answers - Hewings, Martin (Cambridge Univ. Press, 2008)
OCLC: 263453248
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

Breaking the Error Habit - Wood, Stephen Marshall (Universidad Rey Juan Carlos. Servicio de Publicaciones. Dykinson, S.L, 2008)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua); Manual

Cambridge grammar of English: a comprehensive guide; spoken and written English grammar and usage [Cambridge international corpus] - Carter, Ronald; McCarthy, Michael (Cambridge University Press, 2007)
Google-Books-ID: bRXuzgEACAAJ
Keywords: Estudo e ensino; Gramática; Inglés (Lingua); Manual

Student Grammar of Spoken and Written English - Biber, Douglas; Conrad, Susan; Leech, Geoffrey (Longman, 2002)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

English idioms in use: 60 units of vocabulary reference and practice: Self-study and classroom use - McCarthy, Michael (Cambridge University Press, 2002)
Keywords: Estudo e ensino; Inglés (Lingua)

English vocabulary in use: advanced: 100 units of vocabulary reference and practice; self-study and classroom use - McCarthy, Michael (University Press, 2002)
Keywords: Estudo e ensino; Inglés (Lingua); Vocabulario

The Oxford English Grammar - Greenbaum, Sidney (Oxford University Press, 1996)
Keywords: Gramática; Inglés (Lingua); Manual

A Student's English Grammar Workbook - Chalker, Sylvia (Longman, 1992)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

Collins Cobuild English grammar exercises - Shaw, Katy (HarperCollins, 1991)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

Longman English grammar - Alexander, L. G.; Close, R. A. (Longman, 1988)
Keywords: Gramática; Inglés (Lingua)

Spanish/English Contrasts: an introduccion to spanish linguistics - Whitley, M. Stanley (Georgetown University Press, 1986)
Keywords: Español (Lingua); Gramática; Inglés (Lingua); Lingüística; Manual

A Comprehensive Grammar of the English Language - Quirk, Randolph; Greenbaum, Sidney; Leech, Geoffrey; Svartvik, Jan (1985)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

A practical English grammar - Thomson, A. J.; Martinet, A. V. (Oxford University Press, 1982)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

A University Grammar of English - Quirk, Randolph; Greenbaum, Sidney; Quirk, Randolph (Longman, 1973)
Keywords: Estudo e ensino; Gramática; Inglés (Lingua)

The Grammatical structures of English and Spanish - Stockwell, Robert P; Bowen, J. Donald; Martin, John W. (The University of Chicago, 1965)
Keywords: Español (Lingua); Gramática; Inglés (Lingua)